Data Compression Techniques in Wireless Sensor Network: A Survey - Singh, NS; Singh, HJ (International Journal of Computer Sciences and Engineering, 2019)
Wireless sensor networks (WSNs) are highly resource guarded in terms of power supply, memory capacity, communication bandwidth, and processor performance. Compression of sampling, sensor data, and communications can considerably improve the effectiveness of utilization of power supply, memory and bandwidth. Recently, there have been a large number of research proposals describing compression algorithms for WSNs. These research proposals are diverse and involve various compression approaches.. In this paper, we take a step in that direction by presenting a survey of the literature in the area of compression and compression frameworks in WSNs. In addition, open research issues, challenges and future research directions are proposed.